A randomized, double-blind, parallel control study to evaluate the biosimilarity of QL1209 with Perjeta® in healthy male subjects - Sun, Yuanyuan; Yang, Heng; Yang, Xiaoyan; Yang, Shuang; Guo, Can; Chen, Honghui; Cui, Chang; Xiang, Yuxia; Yang, Guoping; Huang, Jie (Frontiers in Pharmacology, 2022)
Purpose: This is the first study to compare the pharmacokinetics, safety and, immunogenicity of QL1209, a biosimilar of Perjeta®. Methods: This study was a randomized, double-blind, parallel-controlled clinical trial evaluating the biosimilarity between QL1209 (specification: 420 mg:14 ml, single use via, manufacturer: Qilu Pharmaceutical Co., Ltd., batch number: 201808001KJL) and Perjeta® (specification: 420 mg: 14 ml, single use via, manufacturer: Roche Pharma AG, batch number: H0309H02). The trial period was 99 days (blood samples for PK were collected 99 days after infusion). Serum concentrations were determined using a validated assay. PK parameters were calculated using a non-compartmental model and analyzed statistically. Anti-drug antibody (ADA)-positive samples were further tested for the presence of neutralization antibody detection (NAb). Results: A total of 137 healthy subjects were administrated. The subjects were randomized 1:1 to receive QL1209 or Perjeta® 420 mg intravenously. The geometric mean ratio (GMRs) for QL1209 versus Perjeta® are 104.14%, 104.09%, and 110.59% for Cmax, AUC0-t, and AUC0-∞, respectively, and their 90% confidence interval (CIs) all fell within the predefined bioequivalence margin 80.00–125%. The incidence of drug-related adverse events was 95.6% and 95.5% in the QL1209 and Perjeta® groups, respectively, also comparable between the two groups. Conclusion: The results of this comparative clinical pharmacology study demonstrated the PK similarity of QL1209 (420 mg: 14 ml) and Perjeta® (420 mg: 14 ml) and there was no significant difference in safety and immunogenicity between QL1209 and Perjeta® manufactured by Roche Pharma AG.